(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Pablo Neruda, one of the most celebrated poets of the 20th century, is renowned for his passionate and politically charged poetry. His work blends themes of love, nature, and social justice, capturing the intensity of human emotion while addressing the struggles of the oppressed. Neruda’s poetry reflects his deep commitment to leftist politics and his role as a public figure in shaping social change, particularly through his affiliation with the Communist Party. Neruda’s political activism is evident in works like Canto General, which celebrates the history and struggles of Latin America. The collection serves as both a tribute to the region’s cultural heritage and a call to action against imperialism and social injustice. His writing was not confined to mere political commentary, but instead embodied a passionate belief in the power of the people and the necessity of revolution. Neruda’s support for various political movements, including his advocacy for the Spanish Republic during the Spanish Civil War, earned him both admiration and controversy.